2009
DOI: 10.1111/j.1399-0004.2009.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mutational analysis of BRCA1/BRCA2 for Korean breast cancer patients: evidence of a founder mutation

Abstract: The BRCA1 and BRCA2 genes are the strongest susceptibility genes identified for breast cancer worldwide. However, BRCA1/BRCA2 have been incompletely investigated due to their large size and the genomic rearrangements that occasionally occur within them. Here we performed a comprehensive mutational analysis for BRCA1/BRCA2 in 206 Korean patients with breast cancer. We analyzed all exons and flanking regions of BRCA1/BRCA2 by direct sequencing and screened deletions or duplications involving BRCA1/BRCA2 by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…These variations have not been reported in the SNP database (http://www.ncbi.nlm.nih.gov/snp) and eight have been reported in the BIC database but are of unknown clinical importance. Among the 13 unclassified variations, 11 variations have been found in previous normal control studies 8,10 and/or in the present study, but there is not reliable functional assay at present. Four different protein prediction programs (PolyPhen, SIFT, PANTHER and SVM) were used to predict the functional consequences of the mutations and obtain diverse results.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…These variations have not been reported in the SNP database (http://www.ncbi.nlm.nih.gov/snp) and eight have been reported in the BIC database but are of unknown clinical importance. Among the 13 unclassified variations, 11 variations have been found in previous normal control studies 8,10 and/or in the present study, but there is not reliable functional assay at present. Four different protein prediction programs (PolyPhen, SIFT, PANTHER and SVM) were used to predict the functional consequences of the mutations and obtain diverse results.…”
Section: Resultsmentioning
confidence: 64%
“…Ahn et al 9 reported that the combination of seven common mutations (BRCA1: c.2433delC, c.3627dupA, c.4065_4068delTCAA, c.5470_5477del8 and c.5496_5506del11insA; BRCA2: c.1399A4T and c.7480C4T) accounted for 62.5% and this suggests the possibility of founder effect. Seong et al 10 analyzed data from previous two large studies 7,9 and reported that another set of seven common mutations (BRCA1: c.390C4A, c.2433delC, c.3627dupA, c.4065_4068delTCAA and c.5496_ 5506del11insA; BRCA2: c.3744_3747delTGAG and c.7480C4T) was recurrent and accounted for up to 43.9% in the pooled population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations